Eco-Food Learning Design: ASSURE Model Instructional Based SDGS to Elementary Students’ Eco-Literacy and Food Literacy - Irni Rachmawati Putri; Rizal Taufik (FONDATIA, 2026)
This study is motivated by the need to develop an ASSURE-based instructional design integrated with the Sustainable Development Goals (SDGs) to enhance elementary students’ eco-literacy and food literacy. The study aims to construct a conceptual framework for Eco-Food Learning Design through three main stages: literature exploration, bibliometric analysis using VOSviewer, and conceptual synthesis. This study adopts a conceptual research design without direct empirical testing. The findings indicate that previous studies have predominantly focused on instructional effectiveness, while the integration of sustainability issues into instructional design remains limited. To address this gap, the proposed Eco-Food Learning Design model systematically embeds sustainability values into the ASSURE stages. The model consists of four logically interconnected components: input, process, integration, and output. Eco-literacy and food literacy are integrated across all instructional stages to create contextual, participatory, and behavior-oriented learning experiences. The study concludes that the proposed model has strong potential to improve students’ environmental awareness, food literacy, and sustainable behavior. This study contributes theoretically to the development of sustainability-based instructional design and offers practical implications for elementary education by providing a structured model for integrating eco-literacy, food literacy, and SDG-oriented learning.